PROFIL USAHATANI POLA PENANAMAN TUMPANG SARI DI DESA SEA KECAMATAN PINELENG - Stella Dompasa; Charles R. Ngangi; Melissa L.G. Taroreh; Tommy F. Lolowang (Universitas Sam Ratulangi, 2014)
ABSTRACTStella Dompasa. Farming Profile Of Inter Cropping System Pattern In Sea Induk Village, Peneleng Sub-District. Under the guidance of Charles R. Ngangi a chairman, and Melisssa L.G Tarore and Tommy F Lolowang as member’s.The objective of this research find out the farmer’s profil from the farming of inter cropping system planting pattern in Sea Induk village. The research used primary data which had been obtained from the respondent farmer by using question list. Data analysis method used in this research is Descriptive Data Analysis. Data collected is presented in table form and then used cost, receipt, and income analysis.The research result showed that this inter cropping farming maight not be underestimated. From the inter cropping farming, the farmer approximately had the income of Rp. 2.888.440, on the first month of crop with the field width of 1,5 ha, with the R/C ratio of 3,24. Therefore the farmer’s outcome of Rp. 1, would give the income of Rp. 3,24.Based on this research, it can be concluded that this inter cropping system farming can give the income to farmer’s continually. So that’s why it needs to do the farming developing in Sea village, and special counseling about inter cropping system farming to ease the farmer’s in new inovation adopting process with the purpose to increase the farmer family’s prosperty.